Improvement of WMS Functionality, Aiming to Minimize Processing Time of Jobs in Grid Computing - Pilkauskas, V.; Plestys, R.; Vilutis, G.; Sandonavicius, D. (Elektronika ir Elektrotechnika, 2011)
WMS (Workload Management System) algorithm of functionality improvement, based on quality of a cluster and used inperforming large scale computing in GRID network, is presented. Limitations for a minimal number of cluster nodes, a minimal numberof central processors in each node, the largest number of jobs queued and the longest acceptable average time for job execution aredefined in distributed jobs. The total time of time, when a job waits in queue, and time, when it is executed, is evaluated. Validity of thejob certificate and a list of clusters are evaluated additionally. A simulator that evaluates the mentioned factors was created forresearching WMS characteristics. Ill. 5, bibl. 9, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.624